Tinjauan Penerapan Sistem Elektronik Rekam Medis di Rumah Sakit Royal Progress Tahun 2018 - Innocentius Probosanjoyo; Joko Asmoro Widhi; Gama Bagus Kuntoadi (Indonesian of Health Information Management Journal (INOHIM), 2018)
AbstractFrom the observations at Royal Progress Hospital, there were problems regarding the application of electronic medical record systems. The current system seems to be the thing that must be used in a hospital. The development of technology makes medical records that were once in the form of paper now begin to switch to electronics. But the application of electronic medical record systems that conform to standards makes it an interesting matter to be reviewed. Therefore on this occasion the writer will examine about it. The purpose of this research is to identify the application of electronic medical record systems. This research is using qualitative descriptive research methods, which is the data collection techniques based on observations and interviews that will be compared with existing theories. Based on the results of research conducted by the writer, it was obtained that the application of electronic medical record systems in Royal Progress Hospital is not all in accordance with the existing theory yet. Therefore the writer suggest to divert the hospital information system that is now used, especially the electronic medical record system into an electronic health record, so that the creation of better health information management.Keywords: Medical record, electronic medical record systems, hospital informationAbstrakDari hasil observasi di Rumah Sakit Royal Progress terdapat masalah tentang penerapan sistem elektronik rekam medis. Sistem tersebut sekarang ini seakan menjadi hal yang wajib digunakan di rumah sakit. Berkembangnya teknologi membuat rekam medis yang dulunya berupa kertas sekarang mulai beralih ke elektronik. Tetapi penerapan sistem elektronik rekam medis yang sesuai standar menjadikan suatu hal yang menarik untuk ditinjau. Maka dari itu pada kesempatan ini penulis akan meneliti tentang hal tersebut. Tujuan dari penelitian ini adalah mengidentifikasi penerapan sistem elektronik rekam medis di RS. Royal Progress. Di dalam penelitian ini menggunakan metode penelitian deskriptif kualitatif. Dimana dengan teknik pengumpulan data berdasarkan pengamatan dan wawancara yang akan dibandingkan dengan teori yang ada. Berdasarkan hasil penelitian yang dilakukan penulis didapat tentang penerapan sistem elektronik rekam medis di RS. Royal Progress belum semuanya sesuai dengan teori yang ada. Oleh karena itu penulis menyarankan untuk mengalihkan sistem informasi rumah sakit yang sekarang digunakan terutama sistem elektronik rekam medis menjadi rekam kesehatan elektronik supaya terciptanya manajemen informasi kesehatan yang lebih baik.Kata Kunci : Rekam medis, sistem rekam medis elektronik, informasi rumah sakit